Teaching History 11-18 : Understanding the Past 11-18. - Husbands, Chris (McGraw-Hill International (UK) Ltd., 2010)
Teaching and Learning History offers a fresh and distinctive view on the teaching of history in schools at a time when the value of learning about the past is often questioned. Drawing together ideas from research, classroom practice and the voices of learners themselves, it sets out an imaginative and wide-ranging rationale for a view of history as an essential component in the learning of all young people.